Activity of the antioxidant enzyme paraoxonase in Argentinean children living at high altitude. (1st January 2018) - Hirschler, V.; Martín, M.; Oestreicher, K.; Molinari, C.; Tetzlaff, W.; Botta, E.; Boero, L.; Brites, F.; on Behalf of San Antonio de los Cobres Study Group,
ABSTRACT: Background: Children living at high altitude in San Antonio de los Cobres (SAC), Argentina, were shown to have lower high-density lipoprotein cholesterol (HDL-C) levels than Buenos Aires (BA) children. HDL antioxidant capacity is mainly attributed to paraoxonase1 (PON1). Objective: To compare PON1 activity in indigenous SAC vs. BA children. Methods: A cross-sectional study compared 158 SAC vs. 97 BA children (6–16 years). Anthropometric data and lipoprotein profile were measured. PON1 was evaluated employing paraoxon (PON) and phenylacetate (ARE) activity. Results: The prevalence of overweight/obesity was lower in SAC than in BA children (18.3 vs . 30.9%). Triglycerides (1.34 vs. 0.90 mmol/l), apo B (0.84 vs . 0.72 g/l), apo A-I (1.33 vs . 1.27 g/l), and ARE activity (100 vs . 90 µmol/ml/min) were higher, while HDL-C (1.16 vs . 1.32 mmol/l) and PON activity (170 vs. 203 nmol/ml/min) were lower in SAC than in BA. Separate multiple linear regression analyses showed that SAC children had significantly higher triglyceride (Beta −0.38), apo B (Beta −0.34), and ARE (Beta −0.36) plus lower HDL-C (Beta 0.33) and PON (Beta 0.25) compared with BA; adjusted for age, gender, and BMI. Conclusion: SAC showed an unfavorable lipoprotein profile, lower PON and higher ARE activities compared with BA children, suggesting the presence of altered HDL metabolism and antioxidant capacity.